Cardiac biomarkers retain prognostic significance in patients with heart failure and chronic obstructive pulmonary disease. Issue 1 (January 2022) - Vergaro, Giuseppe; Aimo, Alberto; Januzzi, James L.; Richards, A. Mark; Lam, Carolyn S.P.; Latini, Roberto; Staszewsky, Lidia; Anand, Inder S.; Ueland, Thor; Rocca, Hans-Peter Brunner-La; Bayes-Genis, Antoni; Lupón, Josep; et al.
Abstract : Aims: Chronic obstructive pulmonary disease (COPD) is a frequent comorbidity in patients with heart failure (HF). We assessed the influence of COPD on circulating levels and prognostic value of three HF biomarkers: N-terminal pro-B-type natriuretic peptide (NT-proBNP), high-sensitivity troponin T (hs-TnT), and soluble suppression of tumorigenesis-2 (sST2). Methods: Individual data from patients with chronic HF, known COPD status, NT-proBNP and hs-TnT values ( n  = 8088) were analysed. A subgroup ( n  = 3414) had also sST2 values. Results: Patients had a median age of 66 years (interquartile interval 57–74), 77% were men and 82% had HF with reduced ejection fraction. NT-proBNP, hs-TnT and sST2 were 1207 ng/l (487–2725), 17 ng/l (9–31) and 30 ng/ml (22–44), respectively. Patients with COPD ( n  = 1249, 15%) had higher NT-proBNP ( P  = 0.042) and hs-TnT ( P  < 0.001), but not sST2 ( P  = 0.165). Over a median 2.0-year follow-up (1.5–2.5), 1717 patients (21%) died, and 1298 (16%) died from cardiovascular causes; 2255 patients (28%) were hospitalized for HF over 1.8 years (0.9–2.1). NT-proBNP, hs-TnT and sST2 predicted the three end points regardless of COPD status. The best cut-offs from receiver-operating characteristics analysis were higher in patients with COPD than in those without. Patients with all three biomarkers higher than or equal to end-point- and COPD-status-specific cut-offs were also those with the worst prognosis. Conclusions: Among patients with HF, those with COPD have higher NT-proBNP and hs-TnT, but not sST2. All these biomarkers yield prognostic significance regardless of the COPD status. Abstract : Supplemental Digital Content is available in the text